Gabriella Kuruvilla, Maneggiare con cura (Milano, Morellini, 2020, 218 pp. ISBN 978-88-6298-743-1) (Altre Modernità, 2020)
Gabriella Kuruvilla, Maneggiare con cura (Milano, Morellini, 2020, 218 pp. ISBN 978-88-6298-743-1)di Nicoletta Vallorani